Analysis of Co-morbidities in Children with Severe Acute Malnutrition in Eastern Nepal - Thapa, Anil; Shah, Gauri Shankar; Mishra, Om P (Journal of Nepal Paediatric Society, 2016)
Introduction: Malnutrition is a common problem in developing countries and often associated with co-morbidities. The present study was undertaken with objectives of to find out the comorbidities in children with severe acute malnutrition (SAM). Materials and Methods: This was a hospital based study carried in 77 children with SAM, diagnosed on the basis of WHO criteria. Results: The age group of children was 1- 5 years (median age 23 months) with about 39% between 1- 2 years. There were 38 males (49.3%). Low maternal education (60%), overcrowding (60%), lower- middle socioeconomic status (87%) were some of the predisposing factors observed. Pneumonia (51%), acute gastroenteritis (21%) and bacterial meningitis (8%) were common co- morbidities found. Associated abnormal laboratory parameters found were anemia (60%), leucocytosis (38%), hyboalbuminemia (36%) hyponetremia (31%), and hypokalemia (17%). Conclusion: Presence of infections and biochemical abnormalities require urgent attention in SAM cases and appropriate treatment in a hospital setting to improve their survival. J Nepal Paediatr Soc 2015;35(2):99-102